The Role of Counseling in Addressing Domestic Violence and Child Abuse - Adaobi Jennifer Iloakasia (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Domestic violence and child abuse remain critical issues that deeply affect the emotional and psychological well-being of victims. Addressing these problems requires strategic interventions, particularly in the field of counseling. Objective: This study aims to identify how counseling can support victims of domestic violence and child abuse in their emotional and psychological recovery process. Method: A descriptive survey research design was employed. The sample consisted of 98 professional counselors and teachers from secondary schools and colleges, selected using stratified random sampling. Data were collected through a structured questionnaire and validated by expert review. Results: Analysis of variance (ANOVA) revealed a statistically significant result (F = 5.215, p = .025), indicating that early counseling interventions significantly promote emotional healing, enhance communication, and build resilience. These outcomes contribute to reducing the occurrence of domestic violence and child abuse. Conclusion: Counseling plays a vital role in helping victims manage emotional responses, break destructive behavioral patterns, and develop healthier coping strategies. Contribution: This study provides valuable insights into the importance of counseling in addressing domestic violence and child abuse. It contributes to a deeper social understanding of the psychological impacts of such violence and the potential of counseling as a restorative tool.